Chemists and Their Wonders: The Story of the Application of Chemistry to Various Arts and Manufactures - Holmes, F. M. (Frederic Morell), 1851- (S. W. Partridge & Co., 1896)
Presents an overview of popular chemistry and its influence on modern industry. Focuses on the industrial application of chemical principles, excluding the application of chemical research in areas such as medicine and academia. Intended to provide insight into the chemical sciences for the common layperson. Includes highly-detailed engraved illustrations throughout and a catalog of works published by S.W. Partridge and Co. at the book's end. This volume is part of the World's Wonders series created by publishers S.W. Partridge and Co. The work is digitized in its entirety.